LOCAL GOVERNMENT ABILITY AS PREDICTOR OF ANTI CORRUPTION - Ronald Tehupuring (Asia Pacific Fraud Journal, 2019)
In recent years, corruption cases have increased significantly. The case of corruption does not only happen to the central government. However, corruption cases also occur in local governments. To reduce corruption, it takes the ability of local governments in managing local finances. That is, the more competent local government, it can reduce corruption. High- local governments ability use their expertise and skills for resource efficiency in generating local revenue in order to improve the welfare of the people. The purpose of this study examine and analyze the local governments ability as anti corruption predictors. The sampling method uses the aimed sample that is, the local government involved in corruption cases and published by the Attorney General of the Republic of Indonesia in 2016. The analysis uses linear regression test with ordinary least square approach (OLS). The results show that local government ability has a negative and significant effect on corruption.